A decision aid to facilitate informed choices among cataract patients: A randomized controlled trial. Issue 6 (June 2021) - Ye, Guofang; Qu, Bo; Tham, Yih-Chung; Zhong, Yuxin; Jin, Ling; Lamoureux, Ecosse; Congdon, Nathan; Zheng, Yingfeng; Liu, Yizhi
Highlights: Patient decision aid may reduce the acceptance of surgical operation among patients with cataract. Our decision aid did help patients make an informed choice about cataract surgery. Our decision aid reduced decisional conflict without eliciting anxiety and worry. Abstract: Objective: To assess the effect of a patient decision aid on the quality of decision-making for patients with age-related cataracts. Methods: 773 patients with cataracts aged 50–80 years were randomly assigned to receive either the intervention decision aid (including standard information, quantitative information on the possible outcomes of cataract surgery and a value clarification exercise) or the control booklet (including standard information). The primary outcome was informed choice (defined as adequate knowledge and congruency between attitudes and surgical intentions), which was assessed at 2 weeks after intervention via a telephone interview. Results: The decision aid increased the proportion of participants making an informed choice, from 5.68 % in the control group to 27.7 % in the intervention group (P < 0.001). Compared with controls, more participants in the intervention group had adequate overall knowledge about cataract surgery (36.8 % vs. 8.79 % in controls; P < 0.001), and fewer participants intended to undergo surgery (22.5 % vs. 34.1 % in controls; P < 0.001). Conclusion: Use of the patient decision aid may increase the proportion of patients making informed choices. Importantly, it might also reduce the acceptance of operations. Practice implications: Patient decision aids represent a simple and low-cost tool to facilitate informed choice among patients with cataracts.